Development of Multimedia Interactive Learning Based on Problem Based Learning in Thematic Learning Grade IV Elementary School - Retno Utari; Rintis Rizkia Pangestika; Riawan Yudi Purwoko (CV. Rayyan Dwi Bharata, 2023)
Information and Communication Technology (ICT) is becoming an important part of life today. This study aims to (1) describe the stages of developing interactive learning multimedia based on problem-based learning in grade IV thematic learning in elementary school grade IV, (2) find out the feasibility of interactive learning multimedia based on problem-based learning in grade IV elementary school thematic learning. The research method used by the ADDIE RD development model with five stages, namely analysis, design, development, implementation, evaluation. Data collection techniques use interviews, observations, questionnaires, and learning outcomes tests. The results of the study: (1) products in the form of interactive learning multimedia based on problem-based learning in grade IV thematic learning elementary school, (2) the validity results of media validation obtained an average of 3.64 with very valid criteria, (3) Student response questionnaires obtained an average of 3.71 with very practical criteria, and learning test results obtained a percentage of 90% with very effective criteria. Interactive learning multimedia is feasible and effective to use in learning activities.